James R: Lehning: Peasant and French. Cultural Contact in Rural France During the Nineteenth Century. - Knudsen, Anne (Tidsskriftet Antropologi, 1996)
Cultural Contact in Rural France During the Nineteenth Century. Anmeldes af Anne Knudsen.